Islamic and Conventional Banks Stability in Indonesia - Shabeer Khan; Nur Amalia Aziza; Allah Ditta Nawaz (Faculty of Economic and Business, 2024)
Research Originality: The stability of banking institutions is crucial for the overall financial health of a country. The originality of this paper lies in its innovative use of quantile regression analysis to provide a nuanced understanding of the factors influencing bank stability, particularly in the Indonesian context.Research Objectives: This research identifies factors influencing bank stability in Islamic and conventional banks in Indonesia.Research Methods: Utilizing quantile regression analysis to measure the impact of various factors at different quantiles, addressing the existing mixed findings in the literature. This study utilizes 15 years of data, encompassing 61 observations for Islamic banks and 779 observations for conventional banks in Indonesia.Empirical Results: The study identifies impaired loans as the primary determinant of bank stability in Indonesia, with a notably greater impact on conventional banks compared to Islamic banks. Notably, the upper quantile of Islamic banks indicates a decline or a lesser impact on bank stability. The paper additionally concludes that the stability of Islamic banks in Indonesia is comparatively lower than conventional banks.Implications: By offering insights into the different levels of factors affecting bank stability, the study contributes to the existing literature, sheds light on unique dynamics, and highlights potential recommendations for enhancing bank stability, especially in the context of non-performing loans.JEL Classification: C21, C23, G21How to Cite:Khan, S., Aziza, N. A., & Nawaz, A. D. (2024). Islamic and Conventional Banks Stability in Indonesia. Etikonomi, 23(1), 167 – 182. https://doi.org/10.15408/etk.v23i1.33879.